Inovasi Pengolahan Limbah Cair Batik dengan IPAL Ekonomis di Desa Maos Kidul Cilacap - Theresia Evila Purwanti Sri Rahayu; Rosita Dwityaningsih; Murni Handayani; Khoeruddin Witriansyah; Ayu Pramita (Politeknik Negeri Cilacap, 2021)
Wastewater resulted from the batik dying process is known for its environmentally hazardous substances including hazardous natural and synthetic organic matter, suspended particles, and hazardous metal. But in the micro and medium scale batik textile business, wastewater treatment is mostly not carried because it does not give benefit for the owner. Economical wastewater treatment constructions can be an alternative for the business owner for their free operational cost. Batik wastewater treatment ought to be carried out to meet government standards but most importantly to decrease hazardous pollutant’s concentrations so it does not harm the environment. This society service project aims to provide alternatively economical wastewater treatment for batik business owners by applying simples and cheapest yet effective treatment methods to reduce pollutant concentrations in wastewater. Methods applied in this project including sedimentation, filtration, and landfill-bioremediation. The laboratorium analysis result shows that sedimentation and filtration are significantly reduced total suspended solid particles in wastewater from 2450 to 100 mg/L in line with wastewater decoloring from dark blue to clear yellow.